«New Normal» of Students’ Educational Practices in the Coronavirus Pandemic Reality - E. Yu. Kostina; N. A. Orlova (Высшее образование в России, 2022)
The article presents the results of qualitative sociologic survey aimed at analyzing students’ subjective evaluations related to “new” educational practices from the perspective of the experience gained in the pandemic period, as well as the dynamics of changes in the content of these evaluations during the year due to the transition to new learning formats. The purpose of the study is to assess the impact of forced online learning on the transformation of traditional educational practices. Following the results of work with qualitative data, the main trends observed in the informants’ answers are shown – increase of academic workload and, as a consequence, the time spent for its performance; absence of former attitude and concentration of attention on the learning material caused by the impossibility to draw boundaries between private and public, that in its turn had an impact on the quality of education and gave rise to new practices of academic dishonesty and cheating; and as a whole, downturn of psychological wellbeing. Main positive moments named by the informants were increase of the capabilities of the educational field and a certain level of comfort in the sphere of everyday life, logistics and work. It is noted that even with the outright victory over the COVID-19 it will be impossible to return completely to pre-covid variant of organization of educational process; whether we like it or not, electronic educational environments have already become an integral part of our life and higher education. The main questions that must be asked now – which of pre-covid and gained practices should be taken into the future, how to find the balance between intramural and online learning formats. Search for solutions depends to a large extent on the success of interaction and cooperation between the direct participants of educational process. Main method of data collection is semi-structured interviews; field works have been carried out in spring of 2020 and 2021. The interview method made it possible to study the situation in detail as it has developed. Based on the generalization of qualitative data, the substantial characteristics of the informants’ value judgments are formed, strong and weak sides of the learning process related to introduction of new formats of interaction “university – teacher – student”. The ambivalent attitude of students to full-time and distance learning was revealed. The scientific novelty of the study lies in the data acquisition, systematization and analytical generalization of the original material on the transformation of students’ educational practices as a result of a forced mass transition to distance education. The obtained materials provide grounds for clarifying the process and results of these changes and can be used to justify management decisions.